Analisis Rantai Pasok Dan Inovasi Pelayanan Terhadap Daya Saing (Studi Perusahaan Ekspedisi Dikota Sukabumi) - Ilham Maulana; Nor Norisanti; Sopyan Saori (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of supply chain and service innovation on the competitiveness of shipping companies in the city of Sukabumi, partially and simultaneously. Respondents used in this study were branch heads, team leaders, and supervisors, totaling 58 people from 15 shipping companies. The research method used in this study is to use a quantitative method with an associative descriptive approach. By carrying out tests, namely the normality test, t-test (partial) t-test (simultaneous). The results in this study show a positive effect simultaneously between supply chain variables and service innovation on competitiveness with results showing that the F count is greater than the F table where the F count value is 74,448, the F table is 3.16. Partially the supply chain has a positive and significant effect on competitiveness, this is evidenced by T count being greater than T table where the T count is 7,136 > T table 2,002. Service innovation has a positive and significant impact on competitiveness, this is evidenced by T count being greater than T table where the value of T count is 2,296> T table is 2,002.